Sources of the Educational Project. (Journal of Parents and Teachers, 2025)
The article discusses the educational system and the variables that influence the development of an Educational Project. Among these, we find the educational system, the identity and history of the center, and the socio-cultural context. Additionally, a triangle is presented to represent the ideas discussed in the article.
Keywords: educational project; variables; educational system; context